Searching for a competitive niche in Singapore's television production industry. - Nur Hana Ahmad Sarom. (2009)
The 1994 deregulation of the broadcasting industry in Singapore has brought about economic boom in the industry with the influx of foreign broadcasters and post-production houses. Since deregulation, they have flocked to Singapore to set up bases to transmit their programmes to other parts of the world. Thus, a lot of economic activities were created and Singapore is on her way to becoming a broadcast and information hub of Asia. However, a booming broadcast industry requires a television production industry to complement and sustain its growth. Yet, the local television production industry seems incapable of keeping up at the moment. It was not able to keep up with the current pace of development and have lagged behind amidst all the activities. Hence, this study attempts to find out the state of the local television production industry and investigate the factors for its slow growth in a rapidly developing broadcasting industry. Several factors were identified and they are the lack of opportunities, insufficient government support, high costs of production, and the lack of manpower support. These factors contributed to the slow growth of the industry. In addition, this study also provided several recommendations that might improve the situation. The government can help to hasten the growth through intervention and setting guidelines and quotas to create more job opportunities for the production houses. Another recommendation is the entry of another broadcaster which will increase the opportunities for the companies to showcase their programmes.